(untitled) (ESMAT Magazine, 2021)
With views on human rights, in addition to an analysis of the responsibility of the adolescent in conflict with the law, from the normative instruments and the theoretical framework of Juvenile Criminal Law, the proposal of this article is to reflect on the action of the legislator guided by the principle of adequate proportionality and limited to the protection of fundamental legal rights, as well as of the subsidiarity for the minimum socio-educational intervention to the adolescent in conflict with the law. The repressive and punitive action unrelated to the minimum socio-educational measure imposes a sanctioning and pedagogical character that does not fit with the proportional action of the legislator for disrespect to the right to integral protection, considering the international treaties to which Brazil is a signatory. The article presents a theoretical research of a phenomenological nature that allows a critical reflection on the work of the legislator in consonance with the international treaties and the Statute of the Child and the Adolescent to the paradigms of the democratic state of right before the condition of the adolescent like subject of the right with absolute priority